2011
DOI: 10.4014/jmb.1012.12020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Penicillin G on Morphology and Certain Physiological Parameters of Lactobacillus acidophilus ATCC 4356

Abstract: Evidence shows that probiotic bacteria can undergo substantial structural and morphological changes in response to environmental stresses, including antibiotics. Therefore, this study investigated the effects of penicillin G (0.015, 0.03, and 0.06 mg/l) on the morphology and adhesion of Lactobacillus acidophilus ATCC 4356, including the colony morphotype, biofilm production, hydrophobicity, H 2 O 2 formation, S-layer structure, and slpA gene expression. Whereas only smooth colonies grew in the presence of peni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…1, 2). Evidence showed that S-layer production was increased under stress conditions (Khaleghi et al, 2010(Khaleghi et al, , 2011 and medium components (ScharZammaretti et al, 2005). It was found that S-layer proteins were present during all growth phases of Lactobacillus acidophilus M92 under heat stress (Frece et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1, 2). Evidence showed that S-layer production was increased under stress conditions (Khaleghi et al, 2010(Khaleghi et al, , 2011 and medium components (ScharZammaretti et al, 2005). It was found that S-layer proteins were present during all growth phases of Lactobacillus acidophilus M92 under heat stress (Frece et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, all the other S-layer proteins characterized are weakly acidic (Avall-Jaaskelainen & Palva, 2005). Evidence shows that the S-layer protein is important for Lactobacillus acidophilus (Frece et al, 2005;Khaleghi et al, 2010Khaleghi et al, , 2011Kim et al, 2001;Toba et al, 1995).…”
Section: S-layer Protein Slpa Expression and Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…farciminis CNCM I-3699 presents heterogeneous colonies on MRS agar and is described here as a pleomorphic strain constituted of welldefined rough and smooth variants (along with intermediate forms) whose presence depends on environmental atmospheric conditions. Although this phenomenon was initially described as being associated to pathogen adaptation and virulence, spontaneous R and S morphotypes were observed in some lactobacilli having technological or beneficial interests such as L. acidophilus RL8K (Klaenhammer and Kleeman, 1981), L. acidophilus ATCC 4356 (Khaleghi et al, 2011), Lactobacillus amylovorus NCFB 2745 (Whitley and Marshall, 1999), L. brevis ATCC 14869 (Jakava-Viljanen et al, 2002), Lactobacillus johnsonii FI9785 (Horn et al, 2013), L. rhamnosus ATCC 9595 (Péant et al, 2005), Lactobacillus plantarum WCFS1 (Bron et al, 2004), or Lactobacillus sakei (Chiaramonte et al, 2010). Furthermore, similar to the present work, R and S morphotypes of Lactobacillus brevis ATCC 14869 were obtained in the presence or absence of O 2 during cultivation (JakavaViljanen et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…However other cultivation parameters have been shown to allow morphological changes in Lactobacillus strains. In other cases, R and S morphotypes of Lactobacillus strains were isolated by the use of varying energy source carbohydrates (Whitley and Marshall, 1999), or in the presence of penicillin (Khaleghi et al, 2011) or bile salts in broth culture (Bron et al, 2004), or more recently by deleting a small heat shock gene of L. plantarum WCFS1 (Capozzi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%